Tinjauan Hukum Terhadap Masuknya Kapal Nelayan Asing di ZEE Indonesia Berdasarkan UU No. 5 Tahun 1983 Tentang ZEE - Avan Caezhar Prayugo; Marthinus Kainama; Arman Anwar (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The EEZ has the greatest natural wealth potential for Indonesia, so the Indonesian government issues various types of legal products to secure and protect and enforce the law in Indonesian waters, especially in the EEZ area.Purposes of the Research: To analyse the regulation of the entry of foreign fishing vessels in the Indonesian EEZ which is contrary to Law Number 5 of 1983 concerning the EEZ, and to analyze the Security and Supervision of Foreign Fishing Vessels in the Indonesian EEZ based on Law Number 5 of 1983. Methods of the Research: The research method used is normative juridical. by using (state approach) and (statute approach). And sources of primary, secondary and tertiary legal materials as well as literature studies, then analyzed qualitatively.Results of the Research: The results show that the entry of foreign-flagged fishing vessels in the Indonesian EEZ is not prohibited because it is not an Indonesian sovereign territory so that foreign vessels have the right to freedom of navigation in the EEZ, but when in their voyage they carry out prohibited activities such as exploration and exploitation of natural resources. biological and non-biological resources found on the seabed and the soil below it as well as the water column and water space above it (without a permit) is an act of violating the law in Indonesia's EEZ (Article 13 of Law Number 5 of 1983). Securing and supervising foreign fishing vessels in the Indonesian EEZ must be carried out in a synergistic and coordinated manner between the TNI-AL, BAKAMLA and POLRI as well as other authorities in accordance with their respective roles and duties.